Supervisi Akademik dalam Meningkatkan Kinerja Guru pada Sekolah SMK Negeri 1 Sangatta Utara - Darajat, Sakia; Sukamti; Paridah (Indra Institute Research & Publication, 2025)
This study aims to determine and identify the extent of the influence of academic supervision on teacher performance at SMK Negeri 1 Sangatta Utara. Efforts to improve the quality of education need to be carried out gradually by referring to the learning plan. The involvement of all components of education (teachers, principals, communities, school committees, education boards, and institutions) through good planning and realizing programmed education programs. Academic supervision carried out by the Principal has a positive and significant effect on changes in teacher performance. Teacher performance can be improved if the principal's academic supervision in the form of leadership and supervision is improved. This study also reveals the importance of the principal's role in implementing academic supervision consistently and continuously. Through effective academic supervision, the principal can provide the guidance, direction, and support needed to develop teacher competence. This will ultimately have a positive impact on improving the quality of learning and student achievement at SMK Negeri 1 Sangatta Utara. In addition, effective academic supervision can help identify individual teacher professional development needs. This allows the principal to design more targeted training and development programs, according to the specific needs of each teacher. With this more personal and structured approach, it is hoped that a culture of continuous learning can be created among teachers, which in turn will improve the overall quality of teaching at SMK Negeri 1 Sangatta Utara.